2020
DOI: 10.1161/atvbaha.119.313863
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Beta–Mediated Sex Differences in Kawasaki Disease Vasculitis Development and Response to Treatment

Abstract: Objective: Kawasaki disease (KD) is the leading cause of acute vasculitis and acquired heart disease in children in developed countries. Notably, KD is more prevalent in males than females. We previously established a key role for IL (interleukin)-1 signaling in KD pathogenesis, but whether this pathway underlies the sex-based difference in susceptibility is unknown. Approach and Results: The role of IL-1 signaling was investigated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 65 publications
1
46
1
Order By: Relevance
“…The differentially expressed proteins (LCWE vs. PBS control) were then analyzed using IPA upstream regulator analysis (Figure 1C) and STRING database analysis of Gene Ontology (Figure 1D). IL-1b was amongst the top upstream regulators when ranked by Z-score, in line with previous investigations in this model (12)(13)(14)19), and our findings that anakinra treatment suppressed the LCWE-induced proteome changes. STRING analysis identified pathways involved in cellular morphogenesis and cytoskeletal organization (Figure 1D; Supplementary Table 1).…”
Section: The Myocardial Proteome In the Lcwe-induced Kd Vasculitis Model Shows A Distinct Protein Expression Profile Which Is Partially Nsupporting
confidence: 92%
See 2 more Smart Citations
“…The differentially expressed proteins (LCWE vs. PBS control) were then analyzed using IPA upstream regulator analysis (Figure 1C) and STRING database analysis of Gene Ontology (Figure 1D). IL-1b was amongst the top upstream regulators when ranked by Z-score, in line with previous investigations in this model (12)(13)(14)19), and our findings that anakinra treatment suppressed the LCWE-induced proteome changes. STRING analysis identified pathways involved in cellular morphogenesis and cytoskeletal organization (Figure 1D; Supplementary Table 1).…”
Section: The Myocardial Proteome In the Lcwe-induced Kd Vasculitis Model Shows A Distinct Protein Expression Profile Which Is Partially Nsupporting
confidence: 92%
“…STAT3 can be activated by a range of cytokines and growth factors including IL-6, IFNg, TNFa, CSF2, CSF3, IL-10, TGF-b, VEGF and EGF. To determine the possible upstream regulators of STAT3 in the LCWE-induced mouse model of KD vasculitis, we utilized our previously published RNA-seq data (GSE141072) (19) from the abdominal aorta of mice treated with PBS, LCWE or LCWE and anakinra. We analyzed this dataset for the expression of Stat3 and the genes encoding the cytokines and growth factors listed above (Figure 3A).…”
Section: The Stat3 Activator Il-6 Is Enhanced In Lcwe-injected Mice and Regulated By Anakinramentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, IL-1 and NLRP3-related gene transcripts are upregulated in PBMCs from patients with acute Kawasaki disease and are decreased during the convalescent phase of the disease 59 , and an IL1B-gene-related signature is associated with acute phase disease and IVIG resistance 130 . Furthermore, a study has shown that differential expression of IL-1β and related signalling genes might have a role in mediating the sex-based differences seen in patients with Kawasaki disease 131 . In the LCWE mouse model of Kawasaki disease, the activation of caspase 1, IL-1α and IL-1β is key to the development of coronary arteritis, aneurysms, myocarditis and abdominal aorta aneurysms 127,128,132 .…”
Section: Myocarditis Most Attention In Kawasaki Diseasementioning
confidence: 99%
“…Wild-type (WT) C57BL/6 and miR223 −/y (B6.Cg-Ptprc a Mir223 tm1Fcam /J) mice were purchased from Jackson Laboratories. For this study, we only used male animals, as LCWE injection induces more severe and more consistent coronary vasculitis lesions and abdominal aorta aneurysms in male than female mice (25,40). All animals were housed under specific pathogen-free conditions at the animal center of Cedars-Sinai Medical Center.…”
Section: Micementioning
confidence: 99%